A structural approach to G-protein signaling mechanisms: α-subunits - (:unkn) unknown (My University, 2006)
Guanine nucleotide binding proteins regulate a variety of physiological processes, including sensual perception, protein synthesis, hormonal regulation, vesicular and nuclear transport, cell growth and differentiation. They act as molecular mediators, cycling between inactive guanosine diphosphate (GDP)-bound and active guanosine triphosphate (GTP)-bound states. G-proteins are composed of three subunits: α, β, γ, where specificity mainly determined by α.The α-subunit consists of two domains: GTPase domain and α-helical domain. Activation results in conformational changes around so called switch I, II and III regions in GTPase- domain. Interaction of the receptor with the carboxyl terminus of α is clearly important. Carboxy terminus is also shown to be important in effector interaction.
Keywords: 3 D structure; Heterotrimeric G-proteins